Needlestick Injuries Reporting among Clinical Nurses - A. Azadi; M. Anoosheh (Iran University of Medical Sciences, 2007)
Background & Aim: Exposure to blood-borne pathogens by needlestick injuries (NSIs) continues to pose significant risks to healthcare workers (HCW). The number of contaminated NSIs sustained by HCW primarily due to underreporting, is still unclear. Therefore the objective of this study was to investigate the Needlestick Injuries and the rate of reporting among Clinical Nurses. Material ;Method: This cross-sectional study was conducted among nurses in one teaching hospital and one nonteaching hospital in Tehran. To investigate the causes of these injuries 111nurses with using purposive sampling method, were contributed and voluntarily and anonymously filled in a questionnaire on the demographic and professional characteristics. In this study, data regarding the frequency of contaminated needlestick and the rate of reporting the injuries and the reasons for not reporting such injuries, were collected.   Results: According to the findings, 54.1% (n=60) of the subjects had no contaminated injuries and 45.9% (n=51) had experienced at least one contaminated NSI in their period of clinical practices. Thirty-four percent of the nurses experienced 58 contaminated needlestick injuries in the past 12 months (Crude Incidence Rate: 0.52 NSI/nurse/year) . Only 36.8% (n=14) of the nurses who had experienced NSIs in the previous year, were reported all exposures to the needlestiks . The reasons for not reporting injuries consisted of dissatisfaction with follow up (33.3%), low probabilities of the infection risk of the injury source (29.2%), to be busy (12.5%), not familiar with reporting process (16.7%) and low perception of risks (8.3%) . Conclusion: This study suggests that the ferequency of NSIs and the rate of underreporting among Iranian nurses are considerable and it needs to be further investigated. Interventions such as continous training of nursing staff about standard reporting protocols and precautions of the post-exposure procedures might improve reporting of such injuries among nurses